DEVELOPMENT OF A HEALTHY LIFESTYLE THROUGH SPORTS EVENTS IN EDUCATIONAL INSTITUTIONS - Shynkaruk, Viktor; Melnikov, Andrii; Mykhailov, Evgen (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
In today’s world, where health and an active lifestyle are becoming more and more relevant, educational institutions of higher education have the potential to become important centers for the formation of healthy habits in children and youth. However, despite the wide distribution of sports activities in educational institutions, the effectiveness of these initiatives in improving the physical, mental and social well-being of students remains in doubt. The purpose article examines the role of sports events and pedagogical initiatives in the formation of a healthy lifestyle among students of higher education. It is noted that an active lifestyle and regular physical activity are of key importance for the physical, mental and social development of young people. If these values are integrated into the curriculum and the pedagogical process, it can significantly contribute to the preservation and improvement of health. Using the example of the experience of organizing sports events at the National Academy of the State Border Service of Ukraine, the positive influence on the development of a healthy lifestyle among cadets is investigated. Sports events create a favorable atmosphere for physical activity and contribute to the development of a healthy sports lifestyle. They provide an opportunity to engage in a variety of sports, which promotes the development of motor skills and supports physical fitness. In addition, sports activities promote social interactions and support the spirit of cooperation and teamwork among the student community. Participation in sports events acts as a powerful mechanism for attracting people to public life, forming social relationships and connections. Specific relationships in sport, whether interpersonal, intergroup or international, weave individuals into a web of social relationships that go beyond the sport itself. Research methods: The article analyzes various aspects of sports events in institutions of higher education, such as sports teams, physical education classes, sports holidays and tournaments. The effectiveness of these measures in forming positive habits regarding physical activity, healthy eating and general well-being is being investigated. In addition, pedagogical strategies and methods that can contribute to maintaining a healthy lifestyle among students are considered. An important aspect is the creation of a supportive environment in the process of forming healthy habits. Results: Based on the analysis, the article provides recommendations for educational institutions and teachers to improve the programs of sports events and initiatives to support a healthy lifestyle among students.